PENERAPAN COMPLIANCE RISK MANAGEMENT (CRM) ENGINE DALAM PEMERIKSAAN PAJAK DI INDONESIA - Helmi Zus Rizal; Agus Fredy Maradona (RELASI : JURNAL EKONOMI, 2022)
Taxation is still the main source of state financing income with almost 80% of state spending supported by taxes. The Directorate General of Taxes (DGT) as the only tax authority in Indonesia is trying hard to collect state revenues, but for a long time the target charged has not been achieved, and the tax ratio has even decreased. The issue of tax compliance has been in the spotlight as the cause of the decline in tax revenue performance in addition to weakening economic conditions due to the trade war and the Covid-19 pandemic. The OECD in 2011 published a Compliance Risk Management (CRM) guide that can be used by countries around the world to mitigate the level of taxpayer compliance risk. DGT has started implementing CRM since 2014 and in 2019 it was implemented on a national scale using computerization. The CRM developed by DGT is divided into several functions according to process requirements. This research focuses on the application of the CRM engine in tax audits in Indonesia. Data analysis in this study was carried out by collecting data, reducing data, presenting data, and drawing conclusions. As for the credibility test using data triangulation and member check. The results of the study found that the CRM engine helps tax audits in the phase before the audit process is carried out, namely the selection of taxpayers to be audited and risk analysis which can later help tax auditors prepare better Audit Plans and Audit Programs. CRM has a positive perception from tax audit stakeholders, namely the Tax Auditor, Audit Section Staff, including the Supervision Section Staff and Tax Consultant too. The risk analysis process becomes more organized and systematic so that priorities can be determined which will be followed up according to the level of tax compliance risk of each taxpayer. Keywords: Compliance Risk Management, Taxpayers, Audit.